(untitled) (Research in Agriculture Livestock and Fisheries, 2017)
Correction: On 3rd May 2017, the PDF was replaced with a correction on page 51. In the figure at the top of page 51, Channel 6 was added. This study was conducted to explore the present status and problems of fish seed marketing system in Sylhet district, Bangladesh. Data were collected through questionnaire interview from the selected areas during April to September 2016. Brood fishes were collected from wild sources as well as hatchery produced brood fishes also used for seed production. Good length, weight and age of brood fishes were selected for spawning and induced breeding. In nursery, hatchlings were reared for 30-40 days and 37.7% nursery owner practiced single cycle production/year where the average stocking density of seed was found 24.65±3.94 g/decimal (mean±SD). Six different fish seed marketing channels were identified where hatchery owners, nursery owners, forias (retailer) and fish farmers were main stakeholders. The highest (6520 Tk/day) and lowest (355 Tk/day) average income were found in hatchery owner and fish farmer, respectively. Oxygenated bag, big aluminum bowl/container and plastic barrels with continuously agitate the water were used for seed transportation. Maximum 17.67% seed mortality was noticed in hatchery owner and minimum 5.67% in fish farmers. Late breeding season, lack of capital, lack of technical knowledge on hatchery operation and management, poor transport facilities, high transportation cost, high labor cost, lack of training and high price of spawn are identified as some major problems. Res. Agric., Livest. Fish.4(1): 45-54, April 2017